Modeling management of foot and mouth disease in the central United States - McReynolds, Sara W. (Kansas State University, 2013)
The last outbreak for Foot and Mouth Disease (FMD) in the United States (U.S.) was in 1929. Since that time the U.S. has not had any exposure to the disease or vaccination, creating a very susceptible livestock population. The central U.S. has a large susceptible livestock population including cattle, swine, sheep, and goats. The impact of FMD in the U.S. would be devastating. Simulation modeling is the only avenue available to study the potential impacts of an introduction in the U.S. Simulation models are dependent on accurate estimates of the frequency and distance distribution of contacts between livestock operations to provide valid model results for planning and decision making including the relative importance of different control strategies. Due to limited data on livestock movement rates and distance distribution for contacts a survey was conducted of livestock producers in Colorado and Kansas. These data fill a need for region specific contact rates to provide parameters for modeling a foreign animal disease. FMD outbreaks often require quarantine, depopulation and disposal of whole herds in order to prevent the continued spread of the disease. Experts were included in a Delphi survey and round table discussion to critically evaluate the feasibility of depopulating a large feedlot. No clearly acceptable method of rapidly depopulating a large feedlot was identified. Participants agreed that regardless of the method used for depopulation of cattle in a large feedlot, it would be very difficult to complete the task quickly, humanely, and be able to dispose of the carcasses in a timely fashion. Simulation models were developed to assess the impact of livestock herd types and vaccination on FMD outbreaks in the central U.S. using the North American Animal Disease Spread Model (NAADSM), a spatially explicit, stochastic state-transition simulation model. Simulation scenarios with large vaccination zones had decreased outbreak length and number of herds destroyed. Vaccination did not provide additional benefit to control compared to depopulation alone when biosecurity and movement controls were high, however the ability to achieve high levels of biosecurity and movement control may be limited by labor and animal welfare concerns.
Keywords: Foot and Mouth Disease; Foreign Animal Disease; Modeling; Biosecurity; Livestock Contacts; Epidemiology (0766)